DEVELOPMENT OF TRADE IN DIGITAL GOODS IN THE CONTEXT OF RECOVERY ECONOMY OF UKRAINE AND ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS - KUPALOVA, Halyna; GONCHARENKO, Nataliia; Oleshko, EVHENII (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The role and necessity of the development of digital trade is increasing in the condition of extremely difficult conditions of conducting military operations, the destruction of infrastructure. The purpose of the conducted research was to formulate the main measures to intensify the development of trade in digital goods, which should be implemented at different levels of management to restore the economy of Ukraine on the basis of sustainable development. The article systematizes and summarizes the developments of domestic and foreign scientists regarding the theoretical and methodological foundations of intellectual property, trade in digital goods, features of their accounting and taxation, organization, and marketing. The necessity of determining the priority directions of digital trade development, taking into account the modern needs of economic recovery, is substantiated. Attention is focused on the differences between the concepts of digital goods and products, although in scientific publications and practical recommendations they are often equated. The level of digital development in Ukraine compared to other countries of the world is shown. The directions for revitalizing the trade in digital goods through the improvement of digital distribution and ensuring the right of ownership are outlined. The main forms and properties, the differences between trade in digital goods and traditional trade, which must be taken into account in the formation of trade policy, are revealed. Barriers inhibiting the development of trade in digital services in Ukraine have been identified. The main measures to intensify the development of trade in digital goods at the national level of management and at the level of business entities are proposed to restore the economy of Ukraine and achieve the goals of sustainable development. Their implementation will contribute to the acceleration of integration into the Single Digital Space of the EU, the expansion of access to online markets, the formation of a digital environment in Ukraine in accordance with European requirements and standards.